A Pilot Study of Infrared Thermal Imaging to Detect Active Bone Lesions in Children With Chronic Nonbacterial Osteomyelitis. Issue 11 (29th October 2019) - Zhao, Yongdong; Iyer, Ramesh S.; Reichley, Lucas; Oron, Assaf P.; Gove, Nancy E.; Kitsch, Averi E.; Biswas, Debosmita; Friedman, Seth; Partridge, Savannah C.; Wallace, Carol A.
Abstract : Objective: Chronic nonbacterial osteomyelitis (CNO) is an autoinflammatory bone disease. An inexpensive and rapid imaging tool, infrared thermal imaging, was evaluated for its utility to detect active bone lesions in extremities of children with CNO. Methods: Children with suspected active CNO and healthy controls were enrolled. All subjects underwent infrared thermal imaging of the lower extremities. Patients in the CNO group also received a magnetic resonance imaging (MRI) examination. Hyperintensity within bone marrow on a fluid‐sensitive T2‐weighted MRI sequence was considered confirmatory for inflammation. Infrared thermal data were analyzed using custom software by dividing the leg below the knee into 3 equal segments longitudinally and adding the distal femur segment as an equal length above the knee. Median and 95th percentile temperatures were recorded for each leg segment. Temperature differences between inflamed and uninflamed segments in all subjects (both intersubject and intrasubject) were evaluated using a linear mixed‐effects model. Results: Thirty children in the suspected/known CNO group and 31 healthy children were enrolled. In the healthy control group, males had significantly higher temperature in their lower extremities than females ( P < 0.05). There was no difference in temperature detected between inflamed leg segments of patients with CNO versus uninflamed leg segments of the healthy control group. However, within the CNO group, significantly higher temperatures were detected for inflamed versus uninflamed distal tibia/fibula segments ( P < 0.01). Conclusion: Children with active CNO lesions in the distal tibia/fibula exhibited higher regional temperatures on average than healthy extremities. Larger studies are warranted to further evaluate the clinical utility of infrared thermal imaging for CNO detection.